2020
DOI: 10.1038/s42003-020-1007-0
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionarily conserved motif is required for Plasmodesmata-located protein 5 to regulate cell-to-cell movement

Abstract: Numerous cell surface receptors and receptor-like proteins (RLPs) undergo activation or deactivation via a transmembrane domain (TMD). A subset of plant RLPs distinctively localizes to the plasma membrane-lined pores called plasmodesmata. Those RLPs include the Arabidopsis thaliana Plasmodesmata-located protein (PDLP) 5, which is well known for its vital function regulating plasmodesmal gating and molecular movement between cells. In this study, we report that the TMD, although not a determining factor for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 35 publications
3
28
0
2
Order By: Relevance
“…Here, we reported that the transient overexpression of Arabidopsis PDLP5 in N. benthamiana increases the accumulation of callose at PD (Figures 3A,B). The finding is supported by a recent report that the transient overexpression of PDLP5 suppresses the PD-dependent movement of mCherry (Wang et al, 2020). Similar to PDLP5, the transient expression of Arabidopsis PDLP7 also increases callose accumulation at PD in N. benthamiana (Figures 3A,B).…”
Section: Discussionsupporting
confidence: 85%
“…Here, we reported that the transient overexpression of Arabidopsis PDLP5 in N. benthamiana increases the accumulation of callose at PD (Figures 3A,B). The finding is supported by a recent report that the transient overexpression of PDLP5 suppresses the PD-dependent movement of mCherry (Wang et al, 2020). Similar to PDLP5, the transient expression of Arabidopsis PDLP7 also increases callose accumulation at PD in N. benthamiana (Figures 3A,B).…”
Section: Discussionsupporting
confidence: 85%
“…Here, we reported that the transient overexpression of Arabidopsis PDLP5 in N. benthamiana increases the accumulation of callose at PD ( Figure 3A-3B). The finding is supported by a recent report that the transient overexpression of PDLP5 suppresses the PD-dependent movement of mCherry (Wang et al, 2020). Similar to PDLP5, the transient expression of Arabidopsis PDLP7 also increases callose accumulation at PD in N. benthamiana ( Figure 3A-3B).…”
Section: Discussionsupporting
confidence: 86%
“…Certainly, it could be possible that the TMD of those class I formins might have additional functions besides the membrane anchoring. In support of this speculation, a very recent report showed that TMD of Arabidopsis thaliana Plasmodesmata-located protein (PDLP) 5 is involved in the self-interaction of PDLP5 that is essential for PDLP5 to regulate cell-to-cell movement besides its role in membrane targeting ( Wang et al, 2020 ).…”
Section: The Role Of Class I Formins In Regulating the Permeability Omentioning
confidence: 98%